Adaptation of the binding domain of Lactobacillus acidophilus S-layer protein as a molecular tag for affinity chromatography development - Muruaga, Emanuel J.; Uriza, Paula J.; Eckert, Gonzalo A. K.; Pepe, María V.; Duarte, Cecilia M.; Roset, Mara S.; Briones, Gabriel (Frontiers in Microbiology, 2023)
The S-layer proteins are a class of self-assembling proteins that form bi-dimensional lattices named S-Layer on the cell surface of bacteria and archaea. S-layers play an important role in cell adhesion, environmental protection, and bacterial-host interaction. The protein SlpA which is the major constituent of the Lactobacillus acidophilus S-layer contains in its C-terminus region (SlpA284-444), a protein domain (named here as SLAPTAG) responsible for the association of SlpA to the bacterial surface. SLAPTAG was adapted for the development of a novel affinity chromatography method: the SLAPTAG-based affinity chromatography (SAC). Proteins with different molecular weights or biochemical functions were fused in frame to the SLAPTAG and efficiently purified by a Bacillus subtilis-derived affinity matrix (named Bio-matrix or BM). Different binding and elution conditions were evaluated to establish an optimized protocol. The binding equilibrium between SLAPTAG and BM was reached after a few minutes of incubation at 4oC, being the apparent dissociation constant (KD) of 4.3 µM, a value which was like other apparent KD estimated for different S-layer proteins and their respective bacterial cell walls. A reporter protein (H6-GFP-SLAPTAG ) was used to compare SAC protein purification efficiency against a commercial immobilized-metal affinity chromatography observing no differences in protein purification performance. The stability and reusability of the BM were evaluated, determining that the matrix was stable for more than a year, being possible to reuse BM five times without a significant loss in its performance. Additionally, we explored the recovery of bound SLAP-tagged proteins by proteolysis using a SLAP-tagged version of the HRV-3c protease (SLAPASE) that released the untagged GFP while the cut SLAPTAG and the SLPASE were retained in the BM. As an alternative, iron nanoparticles were linked to the BM, and the resulting BMmag was successfully adapted for a magnetic SAC, a technique that can be potentially applied for high-throughput-out protein production and purification.